High-strength SiC joints with a novel in-situ formed SiC/Al4SiC4 joining filler. Issue 15 (December 2020) - Liu, Junwen; Zhou, Xiaobing; Tatarko, Peter; Yuan, Qin; Chen, Ke; Wu, Haibo; Huang, Zhengren; Huang, Qing
Abstract: The in-situ formed SiC/Al4 SiC4 joining layer was used to join monolithic SiC using an electric field-assisted sintering technique. A multiphase powder of Al4 C3 /SiC/Al4 SiC4 was used as the initial joining material to obtain the in-situ reaction layer of SiC/Al4 SiC4 via the appropriate interface reactions. The bending strength as high as 240.5 ± 6.6 MPa was obtained for the sample joined at 1800 °C, which was higher than the strength of the un-joined SiC matrix. Sound joints were obtained when Al4 C3 was completely transformed to Al4 SiC4, and a fully dense SiC/Al4 SiC4 joining layer was consolidated. The integration of the joining layer with the SiC matrix was improved by a high amount of liquid phase formed at the interface. The proposed SiC/Al4 SiC4 joining layer, with good thermal matching with SiC matrix, shows a great potential to be applied as a joining material for SiC-based ceramic matrix composites.